Functional seizures are not less important than epilepsy - Ali A. Asadi-Pooya; Francesco Brigo; Benjamin Tolchin; Kette D. Valente (Epilepsy & Behavior Reports, 2021)
Functional seizures (FS) are frequently encountered in neurology clinics, often affect young adults, and have significant negative impacts on many aspects of a person’s life. In the current narrative review, we searched the literature regarding some of the consequences of FS (i.e., psychiatric comorbidities, social consequences, costs that are associated with the condition, cognitive impairment in patients with FS, the quality of life of the people with FS, and the increased risk of mortality that is associated with FS). Evidence shows that FS have significant negative consequences, comparable in their magnitude to those affecting patients with epilepsy. The clinical and scientific communities should take steps to address these consequences through clinical care and research that prioritizes, facilitates, and expedites evidence-based diagnosis and treatment for FS.